Frustrated van der Waals heterostructures - Tawfik, Sherif Abdulkader (Nanoscale, 2024)
Geometrical frustration results from the packing of constituents in a lattice, where the constituents have conflicting forces. The phenomenon is known in glass materials, and this work expands the concept of geometrical frustration into the realm of van der Waals two-dimensional materials. Using density functional theory with the r SCAN + rVV10 exchange-correlation potential, we find a number of two-dimensional heterostructures with alternating strains, where one layer is strained and the adjacent layer is compressed. We adopted three structural stability criteria to find synthesisable candidate materials: phonon dispersion of the individual layers, comparing the thermodynamic stability of this class of materials, frustrated van der Waals heterostructures, with the non-frustrated counterparts, and molecular dynamics simulations. These criteria were applied to 7 frustrated van der Waals heterostructures, identifying one material that is potentially stable. We discuss possible fabrication pathways for creating this class of materials.